Digitalisasi Marketing Produk Songket Desa Limbang Jaya, Ogan Ilir untuk Penguatan Ekonomi Kreatif di Pedesaan - Agustina Bidarti; Eka Mulyana; Azqia Wardana; Dedi Irwanto (Universitas Muhammadiyah Jember, 2026)
Limbang Jaya Village, Tanjung Batu District, Ogan Ilir Regency, is one of Sriwijaya University's fostered villages, boasting creative economic potential based on local culture, particularly Palembang songket crafts. The goal: This activity aims to change the attitudes and behaviors of participants by providing training in packaging, branding, and pricing songket products. Furthermore, increasing the capacity of business actors in digital marketing through WhatsApp Business, Instagram, and local marketplaces, as well as creating digital catalogs and promotional content, will lead to the formation of a songket craftsman business group in Limbang Jaya Village. Method: Face-to-face outreach activities, visits, mentoring, and developing digital marketing for songket products in Limbang Jaya Village, Ogan Ilir. The activity, attended by 20 songket artisans from Limbang Jaya Village, will take place from July to November 2025. Results: The results of the digital marketing assistance program for songket products were able to strengthen and improve the rural creative economy of Limbang Jaya Village, Ogan Ilir. Through this digital innovation, songket produced by Limbang Jaya Village craftsman can increase not only songket production but also songket marketing, which has been a major obstacle for artisans. Thus, digital songket marketing has become a strategy for artisans to market their products through online platforms such as social media, marketplaces, and websites while simultaneously improving and strengthening the rural creative economy of Limbang Jaya.